Harnessing the Power of CAR-NK Cells: A Promising Off-the-Shelf Therapeutic Strategy for CD38-Positive Malignancies - Asadi, Maryam; Kiani, Razie; Razban, Vahid; Faraji, Seyed Nooreddin; Ahmadi, Amirhossein; Fallahi, Jafar; Ramezani, Amin; Erfani, Nasrollah (Iranian journal of immunology, 2023)
CD38 is highly expressed on multiple myeloma (MM) cells and has been successfully targeted by different target therapy methods. This molecule is a critical prognostic marker in both diffuse large B-cell lymphoma and chronic lymphocytic leukemia. We have designed and generated an anti-CD38 CAR-NK cell applying NK 92 cell line. The approach has potential application as an off-the-shelf strategy for treatment of CD38 positive malignancies. A second generation of anti-CD38 CAR-NK cell was designed and generated, and their efficacy against CD38-positive cell lines was assessed in vitro. The PE-Annexin V and 7-AAD methods were used to determine the percentage of apoptotic target cells. Flow cytometry was used to measure IFN-γ, Perforin, and Granzyme-B production following intracellular staining. Using in silico analyses, the binding capacity and interaction interface were evaluated. Using Lentivirus, cells were transduced with anti-CD38 construct and were expanded. The expression of anti-CD38 CAR on the surface of NK 92 cells was approximately 25%. As we expected from in silico analysis, our designed CD38-chimeric antigen receptor was bound appropriately to the CD38 protein. NK 92 cells that transduced with the CD38 chimeric antigen receptor, generated significantly more IFN-γ, perforin, and granzyme than Mock cells, and successfully lysed Daudi and Jurkat malignant cells in a CD38-dependent manner. The in vitro findings indicated that the anti-CD38 CAR-NK cells have the potential to be used as an off-the-shelf therapeutic strategy against CD38-positive malignancies. It is recommended that the present engineered NK cells undergo additional preclinical investigations before they can be considered for subsequent clinical trial studies.